2020
DOI: 10.1177/1359105320962262
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of cognitive behavioral therapy compared with diabetes education for diabetic peripheral neuropathic pain

Abstract: A randomized controlled trial compared cognitive behavioral therapy (CBT) and diabetes education (ED) as an adjunctive treatment for diabetic peripheral neuropathic pain (DPNP). We examined change from baseline to 12- and 36-week follow-up in overall pain intensity (NRS), neuropathic pain intensity/quality, pain interference, and mental health functioning, among others. Although CBT participants demonstrated improvement in pain intensity NRS, there were no between-condition differences at either follow-up. CBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
16
0
2
Order By: Relevance
“…In recent 2 years, a large number of clinical studies had taken CBT as a management measure of different kinds of pain, including mixed unlocated chronic pain [ 7 18 ], back pain [ 19 , 20 ], low back pain [ 21 – 26 ], chronic pancreatitis [ 27 ], fibromyalgia [ 28 , 29 ], functional abdominal pain [ 30 ], trigeminal neuralgia [ 31 ], haemophilia pain [ 32 ], osteoarthritis pain [ 33 35 ], perioperative pain [ 36 – 39 ], orofacial pain [ 40 ], diabetic peripheral neuropathic pain [ 41 ], and provoked vestibulodynia [ 42 ]. Previous studies on structural changes in the brain of patients with chronic pain indicated the presence of neuroplasticity in areas associated with the experience and anticipation of pain [ 43 ].…”
Section: Structural and Functional Changes Of The Brain Due To Cbtmentioning
confidence: 99%
“…In recent 2 years, a large number of clinical studies had taken CBT as a management measure of different kinds of pain, including mixed unlocated chronic pain [ 7 18 ], back pain [ 19 , 20 ], low back pain [ 21 – 26 ], chronic pancreatitis [ 27 ], fibromyalgia [ 28 , 29 ], functional abdominal pain [ 30 ], trigeminal neuralgia [ 31 ], haemophilia pain [ 32 ], osteoarthritis pain [ 33 35 ], perioperative pain [ 36 – 39 ], orofacial pain [ 40 ], diabetic peripheral neuropathic pain [ 41 ], and provoked vestibulodynia [ 42 ]. Previous studies on structural changes in the brain of patients with chronic pain indicated the presence of neuroplasticity in areas associated with the experience and anticipation of pain [ 43 ].…”
Section: Structural and Functional Changes Of The Brain Due To Cbtmentioning
confidence: 99%
“…Otis,2013 [20] 12 8 62.8 CBT treatment as usual / 4months ② Higgins,2020 [21] 24 23 62.3 CBT Education 12weeks 36weeks ② Evans,2003 [26] 12 21 46.5 CBT SPI 6weeks / ② Gale,2002 [18] 4 21 / CBT Nerve block 7weeks / Wetherell,2011 [19] 57 57 54.9 ACT CBT 4weeks 6months ② Hasenbring,1999 [27] 11 12 42.7 RCBT biofeedback / 18months ② Heutink,2012 [25] 24 30 39.5 CBT Waiting list control 3months 6months 纳入研究&发表时间 例数(n) 年龄/岁 干预措施 治疗时间 随访时间 结局指标 试验组 对照组 实验组 对照组 Dehestani,2019 [28] 15 15 39.7 CBT Blank control 10weeks 19weeks 常国胜,2016 [30] 22 22 69.3 认知行为疗法 暗示疗法 8周 6个月 王平,2015 [31] 19 18 51.3 认知行为疗法 睡眠卫生教育 5周 / 武绍远,2006 [29] 30 34 46.3 认知药物治疗 药物治疗 / 2年 ③ 朱莲芳,2019 [23] 48 48 48.92 认知行为疗法 常规干预 / 3个月 杨亚娟,2015 [24] 40 41 49.4 认知行为疗法 常规护理 1个月 / 冯丽娜,2019 [32] 100 100 49.9 认知行为疗法 常规护理 / / ③ 刘振东,2011 [22]…”
Section: 3.文献筛选与资料提取unclassified
“…First, the premise of the interpolation estimation of the Kriging sensor information is that the regional characteristic z is continuous, uniform, and unique. For any sensing information sampling point (x, y) in the area, the expectation c and the variance σ 2 are consistent [17,18]. For any sensing information sampling point, formulas (7) and ( 8) can be obtained:…”
Section: Sensing Information Kriging Interpolationmentioning
confidence: 99%